Analisis Kebijakan Modal Kerja, Likwiditas, Dan Rentabilitas Pada Perusahaan Semen Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Rodhiyah Hariadi (JURNAL ILMU SOSIAL, 2017)
Business companies are demanded to get optimum profit, so they can divide their profit to shareowner. One way to manage their budget by deciding working capital strategy. The strategy will be faced in tradeoff between liquidity and profitability. A correct working capital strategy will lead to maximum profit. Instead, most companies get over liquidity, and lower profitability. In this paper we are going to analyse liquidity and profitability from Indonesian cement companies which registered in BEI(Bursa Efek Indonesia). Financial statements from those companies, such as Semen Indonesia, Semen Holcim, Semen Indocement, and Semen Baturaja during 2012, 2013, 2014, and 2015 is analyst using cross-sectional and time series. During 4 years, those companies shows a consistency of using the same working capital strategy. Both Indonesian cement and Holcim using an aggressive approach, while Indocement and Baturaja using conventiobal approach.